A matter of style? Parenting behaviors of mothers of typically-developing children, children with mild intellectual disability, and deaf or hard-of-hearing children. Issue 1 (2nd January 2023) - Smogorzewska, Joanna; Osterhaus, Christopher
ABSTRACT: Are there categorically distinct parenting behaviours that differ between families with children with and without disabilities (mild intellectual disability [MID], deaf or hard of hearing children [DHH])? A study involving 719 children and their families assessed mothers' responses to the Parenting Styles and Dimensions Questionnaire and children's language skills at 8 and 9 years. A latent class analysis revealed three discrete classes of parenting behaviours: (1) authoritative, (2) mildly authoritative, and (3) inconsistent or neglecting. The latter class comprised around 10% of the mothers, across all groups. The behaviours that were associated with this class, however, differed across groups: In families with children without disability, it was characterized by inconsistent (authoritarian and permissive) behaviours; in families with children with disabilities, it is best described as neglecting. A high level of education was related to better parenting behaviours, and in children with DHH, neglecting parenting was associated with poor language development.